2015
DOI: 10.1002/jmrs.132
|View full text |Cite
|
Sign up to set email alerts
|

The provision of enteral nutritional support during definitive chemoradiotherapy in head and neck cancer patients

Abstract: Combination chemoradiation is the gold standard of management for locally advanced squamous cell carcinomas of the head and neck. One of the most significant advantages of this approach to treatment is organ preservation which may not be possible with radical surgery. Unfortunately, few treatments are without side‐effects and the toxicity associated with combined modality treatment causes meaningful morbidity. Patients with head and neck cancer (HNC) may have difficulties meeting their nutritional requirements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
0
14
0
2
Order By: Relevance
“…The ESPEN guideline recommends tube feeding in RT-induced severe mucositis or in obstructive tumors resulting in dysphagia, anticipating inadequate energy intake [14]. According to the systemic review, the provision of enteral nutrition support via a tube inserted is suggested once oral intake declines below 50% from the energy requirements or once >5 kg of weight loss has occurred from the baseline [33].…”
Section: Discussionmentioning
confidence: 99%
“…The ESPEN guideline recommends tube feeding in RT-induced severe mucositis or in obstructive tumors resulting in dysphagia, anticipating inadequate energy intake [14]. According to the systemic review, the provision of enteral nutrition support via a tube inserted is suggested once oral intake declines below 50% from the energy requirements or once >5 kg of weight loss has occurred from the baseline [33].…”
Section: Discussionmentioning
confidence: 99%
“…Consideration of the psychological factors is increasing in the field of gastric tube implantation [ 13 ]. Incorrect stomach tube insertion causes physical pain as well as great mental tension and psychological fear [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correct nutritional support can help patients improve their nutritional status, prevent complications, facilitate recovery from inflammation, increase the survival rate of the flap, and shorten the hospitalization time [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, a rapid screening method for muscle mass such as bioelectrical impedance instead of more advanced imaging methods would be suitable for this purpose. Nowadays standard nutritional intervention includes the administration of tube feeding (TF) to stabilize weight loss when oral intake is impaired throughout the total course of HNC therapy . It is expected that TF partially limits loss in FM.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays standard nutritional intervention includes the administration of tube feeding (TF) to stabilize weight loss when oral intake is impaired throughout the total course of HNC therapy. 11 It is expected that TF partially limits loss in FM. However, optimizing and maintaining muscle mass might require additional anabolic and/or anti-catabolic ingredients and/or interventions besides TF.…”
Section: Introductionmentioning
confidence: 99%